IMPLEMENTASI BIMBINGAN KELOMPOK DENGAN TEKNIK ROLEPLAY DALAM UPAYA PENANGANAN NEGATIVE CONFORMITY PADA WARGA BINAAN DI LAPAS KELAS III RANGKASBITUNG - Andreas Deli; Arga Satrio Prabowo; Raudah Zaimah Dalimunthe; Angga Sugara Febriantiko (Jurnal Manajemen Pendidikan, 2026)
This study aims to identify the mental health conditions of inmates and describe the implementation of group guidance services based on the results of the General Community Problem Identification Instrument (Alat Ungkap Masalah or AUM) at Class III Rangkasbitung Correctional Institution. The study employed a Participatory Action Research (PAR) approach involving 50 inmates selected through purposive sampling. Data were collected using the General Community AUM instrument to identify various problems experienced by the inmates. The findings revealed that Social Relationships (HSO), Family Conditions and Relationships (KHK), and Personal Self (DPI) were the most dominant problem areas. These issues were related to difficulties in social interaction, longing for and conflicts within the family, as well as personal challenges that potentially affected the inmates’ mental health. Based on the identified needs, group guidance services were implemented to assist inmates in understanding and managing their problems. The implementation of the services showed that inmates became more open in expressing their feelings, were able to share experiences with other group members, and developed greater self-awareness regarding their personal conditions. Therefore, need-based group guidance services can make a positive contribution to supporting inmates’ mental health and the rehabilitation process at Class III Rangkasbitung Correctional Institution.